Effectiveness of the management system in accredited laboratory as a tool to enhance competitiveness - Joanna Wierzowiecka (Foundations of Management, 2013)
The situation on the market of laboratory services in Poland is growing rapidly. In order to stay in this difficult market, one shall convince potential customers to his/her competences and quality of services. Testing or calibration laboratories, wishing to assert its position in the market, introduce the management system based on the PN-EN ISO/IEC 17025:2005 standard, the so-called 'General requirements for the competence of testing and calibration laboratories', and then apply for the certificate of accreditation in the Polish Centre for Accreditation (PCA) [14]. In order to maintain accreditation, as well as to maintain a competitive advantage, laboratories must prove that the management system is effective, which is the matter of this article. The first part presents the analysis of concepts on the effectiveness of the quality management systems and their improvement, in particular those set out in the standards of ISO 9000 series, as well as in the ISO/IEC 17025 standard (in the past and present). In the following part one identified and described the PN-EN ISO/IEC 17025:2005 standard on the effectiveness of the management system in the accredited laboratory (including the involvement of top management and quality policy, internal audits, corrective and preventive actions, evaluation of the effectiveness of training, quality control tests). Then one showed how to assess the effectiveness of the management system, which shall or may be used by the accredited laboratory (i.e. internal audit, self-assessment, management review, surveys and financial appraisal).
Keywords: 650; accredited laboratory; ISO/IEC 17025; quality management system; effectiveness of the management system